A Keyword-Set investigate System for Peer-to-Peer Networks - Rajeyyagari, Sivaram (International Journal of Psychosocial Rehabilitation, 2009)
The Keyword-Set Search System (KSS) is a Peer-to-Peer (P2P) keyword look for sys-tend that uses a circulated wrong side up index. The main challenge in a distributed index and search system is sentence the right proposal to partition the index across the nodes in the network. The most understandable scheme would be to partition the index by keyword. A keyword partition index requires that the list of index entries for each keyword in a search be retrieved, so all the lists can be joined; only a few nodes need to be contact, but each sends a potentially great amount of information, The document list for each set of keywords is then fetched from the network. The lists are intersected to compute the list of similar documents. The list of index entry for each set of words is smaller than the list of entrance for each word. Thus look for using KSS results in a slighter query time over head.